PERAN PEMERINTAH DESA DALAM MENUNJANG PENDAPATAN MASYARAKAT PETANI JAGUNG DI DESA DULOHUPA KECAMATAN BOLIYOHUTO KABUPATEN GORONTALO - Akbar, Muhammad Firyal; Mohi, Widya Kurniati (CosmoGov, 2017)
This research was conducted at the office of Dulohupa Village ofBoliyohuto District. The village government role in community development in the village Dulohupa Boliyohuto District of Gorontalo district, very important to support the conditions of this village because most of the people in this village have subsistence corn farmers so as to enable the empowerment of corn plants.The aims of this research were to determine and analyze the extent of countryside government and factors that encourage and inhibit the role of countryside government in supporting the income of corn farmer at Dulohupa village, Boliyohuto sub district of Gorontalo district. The results showed that the village government Doluhupa plays an important role to determine the appropriate steps to increase incomes of farmersâ corn or empower the people in the village of the District Dulohupa Boliyohuto.